Residential segregation and spatial social division: variables for an analysis of urban structure in Puerto Vallarta, México (2011)
The article presents the results of a research dealing with spatial and residential segregation in Puerto Vallarta, México. Based on local census and general housing surveys data provided by the National Institute of Statistics, Geography and Informatics (INEGI, in Spanish) and, methodologically, on the analysis of principal components with the Statistical Package for Social Sciences (SPSS), the researchers found four types of residences, according to their construction materials, size, utility quality and household income, to elaborate a series of maps that show their position in relation to the Basic Geo-statistical Areas of the city (AGEBS, in Spanish). As a conclusion, it is made clear that the resulting maps provide valuable knowledge and information about the city, since they reveal the zones with the best offer of utilities and urban networks, as well as those more precarious, the lack of infrastructure and public amenities, poor utility quality and public service deficiencies.